2021
DOI: 10.3389/pore.2021.640936
|View full text |Cite
|
Sign up to set email alerts
|

Tuftelin 1 (TUFT1) Promotes the Proliferation and Migration of Renal Cell Carcinoma via PI3K/AKT Signaling Pathway

Abstract: Tuftelin 1 (TUFT1), a protein functioning distinctively in different tissues, is reported to be elevated in several types of cancers and the elevation of TUFT1 is correlated with unfavorable clinicopathologic characteristics and poor survival. However, the involvement of TUFT1 in renal cell carcinoma (RCC) remains unknown. In the current study, we investigated the role of TUFT1 in RCC and potential underlying mechanisms. RT-PCR and Western blot analysis showed that both the mRNA and protein levels of TUFT1 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…DEGs among different m7G subtypes were enriched in cancer-related pathways, such as the positive regulation of cell adhesion, the positive regulation of vasculature development, cell molecule adhesion, the PI3K–Akt signaling pathway, and the AKT–STAT signaling pathway. PI3K–Akt signaling pathway activation can promote the metastasis and progression of RCC ( Du et al, 2021 ; Lin et al, 2021 ; Zhu et al, 2020 ). We divided the patients into three gene types in accordance with the three m7G subtypes and found significant differences in OS and PFS among the subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…DEGs among different m7G subtypes were enriched in cancer-related pathways, such as the positive regulation of cell adhesion, the positive regulation of vasculature development, cell molecule adhesion, the PI3K–Akt signaling pathway, and the AKT–STAT signaling pathway. PI3K–Akt signaling pathway activation can promote the metastasis and progression of RCC ( Du et al, 2021 ; Lin et al, 2021 ; Zhu et al, 2020 ). We divided the patients into three gene types in accordance with the three m7G subtypes and found significant differences in OS and PFS among the subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…TUFT1 is a well‐known carcinogen in multiple cancers, including hepatocellular carcinoma, 33 renal cell carcinoma (RCC), 34 and PC 14 . In this study, TUFT1 was highly expressed in PC.…”
Section: Discussionmentioning
confidence: 80%
“…32 In this study, miR-326-3p expression was reduced in PC cells, which was consistent with the findings of a previous study. 31 Combining bioinformatics analysis, luciferase assay, and RIP assay, we verified TUFT1 is a well-known carcinogen in multiple cancers, including hepatocellular carcinoma, 33 renal cell carcinoma (RCC), 34 and PC. 14 In this study, TUFT1 was highly expressed in PC.…”
Section: Discussionmentioning
confidence: 89%
“…Our results revealed that kdelr2b , leap2 , krtcap2 , svep1 , s100a14 , colgalt1 , znf706 , mob1a , tmem200a , and bag2 were identified as hub genes of the PH trait-associated module. Although their functions in myogenesis have not been explored, many of these genes were reported to contribute to the cell proliferation process through different signaling pathways, such as the Akt-mTOR/GSK3β, PI3K/AKT, and ERK1/2 signaling pathways [ 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. In addition, afmid , stip1 , xirp1 , tspan12 , mib2 , tekt4 , glg1 , stac3 , fam117a , and thrap3 were identified as hub genes of the DH trait-associated module.…”
Section: Discussionmentioning
confidence: 99%